Selection for Inpatient Rehabilitation After Acute Stroke: A Systematic Review of the Literature - Hakkennes, Sharon; Brock, Kim; Hill, Keith (WB Saunders, 2011)
Objective: To identify patient-related factors that have been found to correlate with functional outcomes post acute stroke to guide clinical decision making with regard to rehabilitation admission after acute stroke. Data Sources: We systematically searched the scientific literature between 1966 and January 2010. The primary source of studies was the electronic databases Medline, CINAHL, and Embase. The search was supplemented with citation tracking. Study Selection: Two reviewers independently applied the inclusion criteria to identify relevant articles from the citations obtained through the literature search. Eligible studies included systematic reviews of prognostic indicators, studies of prognostic indicators of acute discharge disposition, and studies of rehabilitation admission criteria after acute stroke. Of the 8895 studies identified, 83 articles, representing 79 studies, were included in the review. Data Extraction: One reviewer extracted the data relating to the participants, prognostic indicators, and outcomes. A second reviewer independently checked data extracted with disagreement resolved by a third reviewer. Quality of included studies was assessed for internal and external validity. Data Synthesis: Of the 79 studies, 26 were systematic reviews of prognostic indicators of functional level and/or discharge disposition, 48 were studies of prognostic indicators of acute discharge disposition, and 6 were studies of rehabilitation selection criteria.The methodologic quality of the included studies was generally poor. Age, cognition, functional level after stroke, and, to a lesser extent, continence were found to have a consistent association with outcome across all 3 research areas. In addition, stroke severity was also associated with acute discharge disposition, final discharge disposition, and functional level. Sex and side of stroke appeared to have no association across all 3 of the research areas. Conclusions: This review highlights a number of important prognostic indicators and rehabilitation selection criteria that may assist clinicians in improving selection procedures and standardizing access to inpatient rehabilitation after stroke, although the quality of many studies is low. Further high quality studies and reviews of prognostic indicators and clinician decision making with regards to rehabilitation acceptance are required.